2000
DOI: 10.1007/s002230001169
|View full text |Cite
|
Sign up to set email alerts
|

Dentin Sialoprotein (DSP) Has Limited Effects on In Vitro Apatite Formation and Growth

Abstract: Sialoproteins such as bone sialoprotein (BSP) and dentin sialoprotein (DSP) accumulate at the mineralization fronts in bone and dentin, respectively, suggesting they have some function in the mineralization process. BSP, a highly phosphorylated protein rich in polyglutamate repeats, is an effective nucleator of hydroxyapatite (HA) formation in vitro. The present study examines the effect of DSP, a low phosphorylated but related sialoprotein, on the formation and growth of HA. In vitro, in a gelatin gel diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 38 publications
4
78
0
Order By: Relevance
“…Interestingly, a maximum in calcium phosphate amounts nucleated occurred at 6.5 μg/mL amelogenin and then the amounts precipitated decreased as the amelogenin concentration increased up to 130 μg/mL. This has been observed for other proteins and molecules, where a maximum in amounts of calcium phosphate precipitated in the presence of polyglutamic acid was ~15 μg/mL protein [27], in the presence of dentin sialoprotein at 5 μg/mL [28] and in the presence of citric acid at ratios of 2-12 calcium ions per citric acid molecule [25]. Other studies have shown that high concentrations of amelogenin (15 mg/mL) in a gel matrix [20] and high concentrations of phosphophoryn (100 μg/mL) [29] inhibited calcium phosphate nucleation.…”
Section: Nucleation Behaviormentioning
confidence: 58%
“…Interestingly, a maximum in calcium phosphate amounts nucleated occurred at 6.5 μg/mL amelogenin and then the amounts precipitated decreased as the amelogenin concentration increased up to 130 μg/mL. This has been observed for other proteins and molecules, where a maximum in amounts of calcium phosphate precipitated in the presence of polyglutamic acid was ~15 μg/mL protein [27], in the presence of dentin sialoprotein at 5 μg/mL [28] and in the presence of citric acid at ratios of 2-12 calcium ions per citric acid molecule [25]. Other studies have shown that high concentrations of amelogenin (15 mg/mL) in a gel matrix [20] and high concentrations of phosphophoryn (100 μg/mL) [29] inhibited calcium phosphate nucleation.…”
Section: Nucleation Behaviormentioning
confidence: 58%
“…Two X-Asp bonds are also cleaved in the posttranslational processing of dentin sialophosphoprotein (34). Dentin sialoprotein is a relatively weak HA nucleator (35), whereas dentin phosphoprotein is an extremely effective nucleator (24). Dentin sialoprotein and dentin phosphoprotein exist as individual proteins and are not co-localized in mineralizing tissues (36).…”
Section: Resultsmentioning
confidence: 99%
“…23 On the other hand, DSP has still unclear functions but is involved in mineral nucleation. 17,[24][25][26] The DSPPs are encoded by a 5-exon gene. Exons 2, 3, 4 and the beginning of exon 5 encode for DSP.…”
Section: Dentinogenesis and Dental Biomineralizationmentioning
confidence: 99%